Biobehavioural Determinants of Colitis-induced Anorexia - Kustra, Erika D.H. (My University, 1996)
Although acute inflammation of the colon (colitis) results in a large suppression of eating, the mechanisms underlying this anorexia remain unknown. Since interleukin-1 (IL-1) receptors are implicated in colitis-induced anorexia and since IL-1 stimulates the release of oxytocin (OT), a neuropeptide implicated in the control of eating, I evaluated the role of OT in the rat model of colitis induced by intrarectal infusion of 2,4,6-trinitrobenzene sulfonic acid (TNB). Antagonism of central OT by a specific OT receptor antagonist did not diminish the magnitude or time course of colitis-induced anorexia. Similarly, no elevations in plasma OT levels correlated with the colitis-induced anorexia, which has been interpreted to mean that malaise was not associated with the anorexia. Subsequently, I examined whether the suppression of food intake could be explained by an exaggerated satiety response to the post-ingestive consequences of food intake that normally signal meal termination. To obtain experimental control over post-ingestive consequences, intragastric preloads were delivered prior to a meal. The various preloads used did not result in a greater suppression of food intake in TNB-treated rats. However, these experiments did reveal significant suppression in the rate of intake for rats with colitis, which suggests a possible shift in response to taste. "Taste Reactivity" measures were taken to assess this possibility. Colitis resulted in a specific change in behaviour and movements that are interpreted to indicate that the food was perceived as less positive. Together, these studies suggest that neither central OT, malaise, nor exaggerated response to post-ingestive consequences are mediators of the colitis-induced anorexia. The shift in Taste Reactivity measures suggests the anorexia may be mediated by a change in taste hedonic perception.
Keywords: Psychology; Psychology